Correlation between the Severity of Liver Cirrhosis (Chil-Pugh Score) and QTc Interval Prolongation - Rachmad Aji Saksana; Putut Bayupurnama; Fahmi Indrarti; Neneng Ratnasari; Sutanto Maduseno; Catharina Triwikatmani; Siti Nurdjanah (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2012)
ABSTRACT Background:Liver cirrhosis causes changes in cardiovascular system. Electrographic (ECG) abnormality commonly found in cirrhosis patients is QT interval prolongation. It is part of cirrhotic cardiomyopathy. QTc interval prolongation is correlated to the incidence of life-threatening arrhythmias. The objective of this study was to recognize the correlation between the severity of liver cirrhosis and QTc interval prolongation in patients with liver cirrhosis at Sardjito General Hospital, Jogjakarta.Method: The design of this study was cross-sectional. The subjects were hospitalized patients with liver cirrhosis at the Department of Internal Medicine, Sardjito Hospital, Jogjakarta between January 2011 and March 2012. ECG was performed in all patients and QTc interval was measured. The severity of liver cirrhosis was determined by Child-Pugh score. Spearman correlation analysis was used to determine the correlation between variables of QTc interval prolongation and Child-Pugh score.Results: A total of 73 patients were enrolled, including 51 (69.9%) male and 22 (31.1%) female patients with mean age of 54.05 ± 12.55 years (range 20-80). Liver cirrhosis was caused by hepatitis B virus in 36 (49.3%) patients, hepatitis C virus in 20 (27.4%) patients and other causes in 19 (26%) patients. The Child-Pugh score for liver cirrhosis was found as follows: child A in 10 (13.6%) patients, child B in 27 (36.9%) patients and child C in 36 (49.3%) patients. The correlation between the severity of liver cirrhosis and QTc interval prolongation was weak (r = 0.255; p = 0.029).Conclusion:Severity of liver cirrhosis has a weak positive correlation with QTc interval prolongation. Keywords: liver cirrhosis, QTc interval, Child-Pugh score